2020
DOI: 10.3390/polym12020451
|View full text |Cite
|
Sign up to set email alerts
|

ECM Mimetic Electrospun Porous Poly (L-lactic acid) (PLLA) Scaffolds as Potential Substrates for Cardiac Tissue Engineering

Abstract: Cardiac tissue engineering (CTE) aims to generate potential scaffolds to mimic extracellular matrix (ECM) for recreating the injured myocardium. Highly porous scaffolds with properties that aid cell adhesion, migration and proliferation are critical in CTE. In this study, electrospun porous poly (l-lactic acid) (PLLA) porous scaffolds were fabricated and modified with different ECM derived proteins such as collagen, gelatin, fibronectin and poly-L-lysine. Subsequently, adult human cardiac fibroblasts (AHCF) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 63 publications
0
33
0
Order By: Relevance
“…Electrospun smooth poly(L-lactide) (PLLA) and porous scaffolds were fabricated as previously reported with slight modications. 12,33 For smooth bers, PLLA, M w of $80 000-100 000 (Polyscience Inc, Warrington, PA, USA) was dissolved in 1,1,1,3,3,3-hexauoro-2-propanol (HFIP) (Fujilm Wako Pure Chemical Corporation, Japan) to obtain a 14.5% w/v of PLLA solution, using magnetic stirring for 4 h. The solution was allowed to rest for another 4 h at room temperature (RT) (25 C). PLLA bers were fabricated using an electrospinner (Nanon-O1A MECC Co. Ltd. Fukuda, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrospun smooth poly(L-lactide) (PLLA) and porous scaffolds were fabricated as previously reported with slight modications. 12,33 For smooth bers, PLLA, M w of $80 000-100 000 (Polyscience Inc, Warrington, PA, USA) was dissolved in 1,1,1,3,3,3-hexauoro-2-propanol (HFIP) (Fujilm Wako Pure Chemical Corporation, Japan) to obtain a 14.5% w/v of PLLA solution, using magnetic stirring for 4 h. The solution was allowed to rest for another 4 h at room temperature (RT) (25 C). PLLA bers were fabricated using an electrospinner (Nanon-O1A MECC Co. Ltd. Fukuda, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Bioactive molecules, when used in scaffolds, need to mimic the extracellular matrix (ECM), the supportive structure that surrounds the tissue cells, which is made up of many proteins and proteoglycans gathered in an ordered structure. [11][12][13][14] Electrospun bers of poly(L-lactic acid) (PLLA) and PLLA blends have been used in a wide variety of biomedical applications such as dressings for wounds, scaffolds for tissue (bone, nerve, skin) engineering, drug release and dental applications. 7,15,16 PLLA is a biodegradable and biocompatible polymer that hydrolyzes to lactic acid, a biocompatible metabolic byproduct.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous natural (e.g., collagen, fibrin, and native ECM) and synthetic [e.g., poly(glycerol sebacate), polyurethane, and polyethylene glycol] scaffold materials have been tested for myocardial regeneration. These materials enable fine-tuning of various important tissue properties including degradation kinetics, elastic modulus, porosity, and immune response (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). In addition, several studies have sought to identify or integrate various signaling factors that can modulate cardiac healingespecially cardiomyocyte proliferation-including growth factors (e.g., NRG-1, FGFs, VEGF, IGF-1), ECM components (e.g., Agrin, Fibronectin, Periostin), and modulators of the Wnt and Hippo pathways (31)(32)(33)(34)(35)(36).…”
Section: Recapitulating the Architecture Of The Heart Wallmentioning
confidence: 99%
“…In this case, poly(L-lactic acid) (PLLA), which is a biodegradable polymer, could be an excellent material for designing the hollow nanofibers. [28][29][30][31] To develop such hollow PLLA nanofibers, different approaches were tried in past. However, to the best of our knowledge, limited studies have been reported on template wetting method.…”
Section: Introductionmentioning
confidence: 99%